Pengelolaan Literatur Kelabu (Grey Literatur) di Perpustakaan lingkup Badan Litbang Pertanian - Etty Andriaty; Tuti Sri Sundari (Pusat Perpustakaan dan Penyebaran Teknologi Pertanian, 2012)
Management of Grey Literature in Libraries within Indonesian Agencyfor Agricultural Research and DevelopmentGrey literature is the most current research information source andis the intellectual property of an organization, government agenciesand other science and technology assessment agencies, unpublishedcommercially, and official documents issued in limited copies. Thestudy aimed to find out the management of grey literature in librarieswithin the Indonesian Agency for Agricultural Research andDevelopment (IAARD), which was conducted in April-May 2012 ina descriptive survey. Respondents were 54 IAARD librarians/librarymanagers. The results showed that most of the librarians/librarymanagers knew kinds of library collection of grey literature. Mostlibraries collected grey literature from gifts and of their institutes ownpublications. Registration, cataloging and classification were doneby most libraries. Almost all respondents use the UDC for classification,AGROVOC Thesaurus to determine keywords, and data entry weredone electronically. More than half of respondents had digitized greyliterature. Most of grey literature’s collection were kept separatingfrom other collections. Circulation of the grey literature was the mostservices provided by the respondents.